Synthetic routes towards guanidines of biological interest - Shaw, Julian W. (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
The Rozas laboratory has been interested in the synthesis and biological evaluation of guanidine containing molecules for the past ten years. The application of guanidines as both minor groove binders (MGB) and a2-adrenoceptor (a2-AR) antagonists has been the focus of much of the research conducted. A number of promising results have been discovered in targeting the a2-AR. with a number of effective agonists and antagonists having been synthesised. a2-AR antagonists have proven to be a valid target for the alleviation of symptoms of Major Depressive Order. Historically these guanidines have been prepared by reacting the prerequisite anilines with N,N-bis-tert-butoxycarbonyl-thiourea in the presence of HgCl2 to form the protected aryl guanidines. The use of mercury in such reactions is an obvious drawback and it was decided that its use should be eliminated from the synthesis of biologically active guanidines in Rozas group. The overlying aim of this PhD project was therefore to design and implement the synthesis of guanidine containing compounds without the use of HgCl2.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin